Production of porcine reproductive and respiratory syndrome virus (PRRSV)-resistant genomeedited cloned pigs using CRISPR/Cas9n system - WANG Shaohua; ZHAO Panpan; LIU Tong; DING Biao; LUO Lei; CAO Zubing; ZHANG Yunhai; ZHANG Kun (浙江大学学报. 农业与生命科学版)
Using gene editing technology based on CRISPR/Cas9n system and somatic cell nuclear transfer technology, we constructed a plasmid of two sgRNAs and Cas9 nickase, and green fluorescent protein (GFP) in the same vector followed by transient transfection of porcine fibroblasts. By flow cytometry, the cells expressing GFP were selected, and the GFP positive cells were cultured to single cells. The CD163 edited clones were screened through polymerase chain reaction (PCR) and DNA sequencing, and the positive rate was as high as 90% (18/20). Somatic cell nuclear transfer and embryo transfer were carried out using cells with edited CD163, and two CD163 gene-edited cloned offsprings were obtained.